Sodium butyrate in Irritable Bowel Syndrome - Aleksandra Kołodziej; Wiktoria Zamirska; Nadia Hornig; Aleksandra Cieplak; Zuzanna Czyżewicz (Journal of Education, Health and Sport)
Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder characterized by abdominal pain, bloating, and altered bowel habits. Although its pathophysiology is not fully understood, factors such as gut microbiota imbalance, increased intestinal permeability, and low-grade inflammation are considered key contributors. Sodium butyrate, a short-chain fatty acid produced by bacterial fermentation of dietary fiber, plays an important role in gut health. It supports intestinal barrier function, reduces inflammation, and influences microbiota composition. This review summarizes current knowledge on the role of sodium butyrate in IBS, focusing on its mechanisms of action and clinical relevance. A literature review was conducted using databases such as PubMed and Google Scholar with relevant MeSH keywords. Preclinical and clinical studies indicate that sodium butyrate may help alleviate IBS symptoms by enhancing epithelial integrity and modulating inflammation. However, variations in study design and dosing limit clear conclusions. Further randomized trials are needed to confirm its efficacy and define optimal treatment strategies.